Antibody association in solution: cluster distributions and mechanisms - Sandi Brudar; Leonid Breydo; Elisha Chung; Ken A. Dill; Nasim Ehterami; Ketan Phadnis; Samir Senapati; Mohammed Shameem; Xiaolin Tang; Muhammmad Tayyab; Barbara Hribar-Lee (Taylor & Francis Group, 2024)
ABSTRACTUnderstanding factors that affect the clustering and association of antibodies molecules in solution is critical to their development as therapeutics. For 19 different monoclonal antibody (mAb) solutions, we measured the viscosities, the second virial coefficients, the Kirkwood-Buff integrals, and the cluster distributions of the antibody molecules as functions of protein concentration. Solutions were modeled using the statistical-physics Wertheim liquid-solution theory, representing antibodies as Y-shaped molecular structures of seven beads each. We found that high-viscosity solutions result from more antibody molecules per cluster. Multi-body properties such as viscosity are well predicted experimentally by the 2-body Kirkwood-Buff quantity, G22, but not by the second virial coefficient, B22, and well-predicted theoretically from the Wertheim protein-protein sticking energy. Weakly interacting antibodies are rate-limited by nucleation; strongly interacting ones by propagation. This approach gives a way to relate micro to macro properties of solutions of associating proteins.